IDENTIFICATION OF AUTISM IN CHILDREN USING STATIC FACIAL FEATURES AND DEEP NEURAL NETWORKS - K.P.Lakshmi Priya, I.Jyothirmai, G.Akshaya,Ch. Smitha Chowdary, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Nowadays with the ongoing improvement of synthetic intelligence facial emotion acknowledgment has grown to be greater prominent. The feeling acknowledgment performs a big feature in the interplay era. In verbal exchange technology, the spoken factors really play a one zero.33 of interaction similar to the non-verbal factors plays a 2 zero.33 of interplay. The facial emotion recognition (FER) method is made use of for detecting facial expressions. Face plays a fantastic function in sharing what a person truly feels and furthermore it exhibits inner feeling and his or her intellectual scenario or human component of view. This paper pursuits to decide famous human feelings with the mixture of gender classification and also age estimate. The facial feelings together with thrilled, depressing, disappointed, task, taken aback, impartial emotions are considered as elegant emotions. Here proposes a real-time facial feeling recognition device based totally upon You Look Just Once (YOLO) version 2 styles similar to a squeeze net architecture. The Yolo layout is an actual time object detection device. Right here it was carried out to find out and find out faces in real-time. These photographs are recorded via the usage of anchor boxes for precision. The 2d form is squeezed net and is likewise used for person magnificence and additionally age assessment. It additives excellent, precise item detection in addition to essences pinnacle-diploma attributes that help to advantage high-quality ordinary performance to recognize the image further to locating devices. Both the designs supply proper cease end result than several unique techniques with the large no of wonder layers further to transport all through reputation within the neural network.